Somite Division and New Boundary Formation by Mechanical Strain - Nelemans, Ben K.A.; Schmitz, Manuel; Tahir, Hannan; Merks, Roeland M.H.; Smit, Theodoor H. (iScience, 2020)
Somitogenesis, the primary segmentation of the vertebrate embryo, is associated with oscillating genes that interact with a wave of cell differentiation. The necessity of cell-matrix adherence and embryonic tension, however, suggests that mechanical cues are also involved. To explicitly investigate this, we applied surplus axial strain to live chick embryos. Despite substantial deformations, the embryos developed normally and somite formation rate was unaffected. Surprisingly, however, we observed slow cellular reorganizations of the most elongated somites into two or more well-shaped daughter somites. In what appeared to be a regular process of boundary formation, somites divided and fibronectin was deposited in between. Cell counts and morphology indicated that cells from the somitocoel underwent mesenchymal-epithelial transition; this was supported by a Cellular Potts model of somite division. Thus, although somitogenesis appeared to be extremely robust, we observed new boundary formation in existing somites and conclude that mechanical strain can be morphologically instructive. [Display omitted] •Live chick embryos develop normally under substantial axial strain (>50%)•Mature somites divide into daughter somites, and fibronectin is deposited in between•Mesenchymal cells from the somitocoel transition into epithelial border cells•Mechanical strain can induce border formation and thus affect morphogenesis Poultry Embryology; Mechanical Modeling; Developmental Biology